Akkadische Logogramme - Schramm, Wolfgang (Universitätsverlag Göttingen, 2010)
Reading transliterated akkadian texts sometimes is rather difficult, if the akkadian equivalents of the logograms are not given. This first alphabetic index of akkadian logograms offers help now: it contains the akkadian readings of most logograms, so the time consuming detour through the indexes of sign lists can be avoided in most cases. The circa 5000 entries also record the principal meaning of the akkadian word as well as references to sign lists (Borger, Mesopotamisches Zeichenlexikon or Labat, Manuel d'épigraphie akkadienne) or to akkadian dictionaries. In this way the epigraphic as well as the lexical approach to the text is enhanced. The book (written in German) is designed for students who are interested in akkadian literature, but cannot read cuneiform writing or Sumerian. The 2nd edition was thoroughly revised. In particular, R. Borger's Mesopotamisches Zeichenlexikon is now quoted as the standard sign list for Akkadian.